Comparative analysis of the chloroplast genomes of eight Piper species and insights into the utilization of structural variation in phylogenetic analysis - Li, Jing; Fan, Rui; Xu, Jintao; Hu, Lisong; Su, Fan; Hao, Chaoyun (Frontiers in Genetics, 2022)
With more than 2000 species, Piper is regarded as having high medicinal, cosmetic, and edible value. There also remain some taxonomic and evolutionary uncertainties about the genus. This study performed chloroplast genome sequencing of eight poorly studied Piper species and a comparative analysis with black pepper (Piper nigrum). All examined species were highly similar in gene content, with 79 protein-coding genes, 24 tRNAs, and four rRNAs. They also harbored significant structural differences: the number of SSRs ranged from 63 to 87, over 10000 SNPs were detected, and over 1000 indels were found. The spatial distribution of structural differences was uneven, with the IR and LSC being relatively more conserved and the SSC region highly variable. Such structural variations of the chloroplast genome can help in evaluating the phylogenetic relationships between species, deciding some hard-to-distinguish evolutionary relationships, or eliminating improper markers. The SSC region may be evolving at high speed, and some species showed a high degree of sequence variation in the SSC region, which seriously affected marker sequence detection. Conversely, CDS sequences tended to lack variation, and some CDSs can serve as ideal markers for phylogenetic reconstruction. All told, this study provides an effective strategy for selecting chloroplast markers, analyzing difficult-to-distinguish phylogenetic relationships and avoiding the taxonomic errors caused by high degree of sequence variations.